Ключові облікові показники підприємства в ощадливому виробництві - Колос, Ірина Василівна (My University, 2014)
В статті систематизовано існуючі методики оцінки діяльності підприємства; обґрунтовано критерії відбору облікових показників; запропоновано ієрархічну систему облікових показників для оцінки ефективності функціонування підприємства на засадах ощадливості; розроблено інформаційні моделі оцінки показників. The methodologies for the estimation of activity of enterprise are systematized: 1) recommended by the state; 2) worked out by consulting companies with possible adaptation for enterprise; 3) created by an enterprise as unique. The criteria are reasonable for the selection of results indicators of efficiency of industrial lean enterprise. The hierarchical system of results indicators is offered for estimation efficiency of functioning of lean enterprise: 1) results indicators of efficiency of cell; 2) results indicators of efficiency of value stream; 3) results indicators of efficiency of enterprise. The expedience is well-proven on introduction of the hierarchical system of results indicators; it will provide the timely decision of problem. Information models are designed to assess the hierarchical system of results indicators. The formulas for the calculation of identifying the sources of information (financial, statistical, tax, management accounts, registers, source documents) are given for practical use.
Keywords: кафедра обліку і аудиту; ощадливе виробництво; облікові показники підприємства; lean виробництво